Has J-PARC E07 observed a Ξ1s− nuclear state? - E. Friedman; A. Gal (Physics Letters B, 2023)
The Strangeness S=−2 J-PARC E07 emulsion experiment published recently two new Ξ−–14N capture events, IRRAWADDY and IBUKI, identified by observing weak-decay sequences of pairs of single-Λ hypernuclei and interpreted as Ξ1s− and Ξ1p− nuclear bound states, respectively, with binding energies BΞ−1s=6.27±0.27 MeV and BΞ−1p=1.27±0.21 MeV. Ξ− capture events in emulsion play a major role in determining the Ξ-nuclear and the ΛΛ potential strengths. Here we question the assignment of a Ξ1s− nuclear bound state to IRRAWADDY and offer an alternative assignment as a near-threshold Ξ1p0–14C nuclear bound state, slightly admixed with a Ξ1p−–14N nuclear bound state component corresponding to IBUKI. We also question using IBUKI's BΞ−1p value as is to determine the Ξ-nuclear potential depth. Altogether, Ξ− capture events in 12C and 16O should prove less ambiguous than in 14N.